Photovoice: A Participatory Methodology by Counselor Researchers for Capturing Minor Client’s Perceptions and Experiences as Reflections of Their Self-Concepts - Shaziti, Aman; Amalia, Madihie (Faculty of Cognitive Science and Human Development, 2014)
In-depth exploration on children’s self-concept is crucial because self-concept is able to show how a person thinks about, evaluates or perceives themselves. Children’s self-concept has largely been perceived through the adult’s lenses whereby previous research with children has fundamentally been on children due to them being viewed as inadequate and incomplete therefore unreliable sources. However, this view of childhood has changed with the emergence of the ‘new social studies of childhood’ and the children’s right discourse (the United Nations Conventions on the Rights of the Child, 1989; the Children’s Act, 2004). Children are now viewed as social actors who are ‘experts’ on their own lives with a competence to communicate a unique insight into their experiences and perspectives. Therefore appropriate approaches to include children’s viewpoints are necessary. This paper discusses the concept, methodology, benefits and ethics consideration in using Photovoice to investigate children’s self-concepts. Photovoice is a participatory research methodology with children where children take their own photographs to be used later to elicit discussion or dialogue, enabling their ‘voice’ to be heard. Their own photographs are probably more likely to capture what matters to them thus may yield a more accurate reflection of their self-concepts. A few self-concept theories, development of a concept of self, and self-concept of components are also discussed. In addition, recommendations for future research are suggested.